2018
DOI: 10.1080/17435390.2018.1465139
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation in the pleural cavity following injection of multi-walled carbon nanotubes is dependent on their characteristics and the presence of IL-1 genes

Abstract: (2018) Inflammation in the pleural cavity following injection of multi-walled carbon nanotubes is dependent on their characteristics and the presence of IL-1 genes, Nanotoxicology, 12:6, 522-538, DOI: 10.1080/17435390.2018 Upon inhalation, multi-walled carbon nanotubes (MWCNTs) may reach the subpleura and pleural spaces, and induce pleural inflammation and/or mesothelioma in humans. However, the mechanisms of MWCNT-induced pathology after direct intrapleural injections are still only partly elucidated. In par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Direct injection of long MWCNTs into the pleural cavity induced an acute inflammatory response in the parietal pleura and resulted in significantly increased numbers of total cells and granulocytes in the pleural cavity lavage fluid (PCLF) in mice (Murphy et al 2011). Intrapleural injection of Mitsui XNRI MWNT-7 (MWNT-7), a well-characterized MWCNT preparation with a mean length of 3.86 μm and a count mean diameter of 49 nm caused an inflammatory response in mouse pleura, showing inflammatory infiltration and formation of granulomas (Arnoldussen et al 2018). In two studies, pulmonary administration of MWCNTs by transtracheal intrapulmonary spraying (t.i.p.s.)…”
Section: Inflammation Fibrosis and Cancer Are Major Adverse Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct injection of long MWCNTs into the pleural cavity induced an acute inflammatory response in the parietal pleura and resulted in significantly increased numbers of total cells and granulocytes in the pleural cavity lavage fluid (PCLF) in mice (Murphy et al 2011). Intrapleural injection of Mitsui XNRI MWNT-7 (MWNT-7), a well-characterized MWCNT preparation with a mean length of 3.86 μm and a count mean diameter of 49 nm caused an inflammatory response in mouse pleura, showing inflammatory infiltration and formation of granulomas (Arnoldussen et al 2018). In two studies, pulmonary administration of MWCNTs by transtracheal intrapulmonary spraying (t.i.p.s.)…”
Section: Inflammation Fibrosis and Cancer Are Major Adverse Effectsmentioning
confidence: 99%
“…Intrapleural injection of long MWCNTs induced the formation of a fibrotic layer over the parietal pleura over a period of 4–24 weeks post-exposure in mice with increased thickness and a high content of collagen (Murphy et al 2011). Intrapleural injection of XNRI MWNT-7 also caused fibrosis, indicated by increased collagen fibers, in the visceral pleura in mice on day 28 post-exposure (Arnoldussen et al 2018). Furthermore, transtracheal intrapulmonary spraying of long needle-like MWCNTs once every 2 weeks for 24 weeks in rats enabled MWCNTs to translocate into the pleural cavity, deposit in the parietal pleura, and induce fibrosis in both the visceral and the parietal pleura with thickened lesions composed of collagen fibers (Xu et al 2014; Xu et al 2012).…”
Section: Inflammation Fibrosis and Cancer Are Major Adverse Effectsmentioning
confidence: 99%
“…CNTs can also be administered through intrapleural injection (through the thoracic wall). Research has shown that lengthdependent retention of CNTs in the pleural cavity is able to induce sustained inflammation, progressive fibrosis, and mesothelioma growth (57,68,88). The molecular mechanisms involved in mesothelioma development caused by CNT exposure are considered the same as in asbestos carcinogenesis (57).…”
Section: Intrapleural Injectionmentioning
confidence: 99%
“…Lastly, pro-inflammatory cytokines are released from macrophages due to CNT exposure via frustrated phagocytosis. Mesothelial cells are also damaged by other CNT-induced incidents, including immunosuppressive microenvironment and epigenetics (87,88). All these conditions perturbed by CNTs may contribute to the transformation of healthy mesothelial cells to MPM cells.…”
Section: Mesothelial Cell Damage After Cnt Exposurementioning
confidence: 99%
“…For this reason, an increasing number of in vitro and in vivo studies have been devoted to the evaluation of the pulmonary toxicity of MWCNTs. Studies performed in rodents show that MWCNTs exposure may lead to an inflammatory response and, depending on their physical and chemical properties, the development of fibrosis, granulomas, or lung cancer [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Experiments carried out in cell lines highlight genotoxic effects, transforming potential, and cytotoxicity [ 7 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%